Efeito da Staniocalcina-1 sobre ativação microglial e disfunção mitocondrial na sepse - Joaquim, Larissa da Silva (2019)
Introduction: Sepsis is one of the leading causes of mortality in intensive care units, besides causing acute brain dysfunction, is associated with long-term neurocognitive consequences. Evidences has suggested that the microglial activation and mitochondrial dysfunction are involved in brain dysfunction after sepsis but understanding molecular mechanisms and therapies a major challenge. Given the emerging role of Stanniocalcin-1 (STC-1) a intracrine protein internalized to the mitochondria, and responsible to diminishes superoxide generation through induction of Mithocondrial Uncoupling Proteins-2 (UCP-2) and inflammatory responses, we hypothesized that STC-1 may modulate inflammatory response and UCP-2 expression after microglial activation and attenuate mitochondrial dysfuntion in sepsis. Objective: To evaluate the effect of STC-1 on microglial activation and mitohondrial injury in sepsis. Methods: The microglial cell culture was exposed to LPS (10 μg / ml) and RhSTC-1 at 1, 10, 100, 500 and 1000 ng / ml and cell viability, TNF-α, IL-1β, IL-6, IFN-γ, IL-2, IL-13, IL-10 and IL-18 levels and UCP-2 mRNA expression were evaluated. Sepsis was induced in male Wistar rats using Cecal Ligation and Puncture (CLP), and control rat underwent (sham) surgery. RhSTC-1 (20, 50 and 100 ng / kg) was administered intracerebroventricularly. Twenty-four hours after CLP, hippocampus was obtained and assayed for mitochondrial respiratory chain and Creatine kinase (CK) activity. Results: STC-1 increase cell viability, decreased TNF-α, IL-1β, IL-6, IFN-γ levels and did not interfered in UCP-2 level in microglial cells. In rats, STC-1 at the highest doses restored complex I, II and CK activity after in sepsis the hippocampus. Conclusion: Our data provide the first experimental demonstration that STC-1 was able to reduce the neuroinflammation in vitro and sepsis-induced brain dysfunction in rats by decreasing mitochondrial dysfunction and CK activity alteration.